The Role of Mazoon Al Ilm Award for Excellence and Educational Creativity (Outstanding Teacher Category) in Enhancing Teaching Performance Among Teachers at Mazoon Al Ilm School in South Al Batinah Governorate - المعولية, ايمان بنت محمد بن زيد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The current study aimed to find out the role of the Mazoon El Elm Award for Excellence and Educational Creativity in improving the educational (teaching) performance of female teachers at the Mazoon El Elm School, and to detect the differences between the average scores of the study sample responses about the role of the Mazoon El Elm Award for Excellence and Educational Creativity in improving the educational (teaching) performance of female teachers At Mazoon Al-Ilm School, it is attributed to the variables (educational qualification, number of years of experience, job title - specialization). Where the descriptive analytical approach was used, and the questionnaire was a tool for the study, as it was distributed to (27) teachers from the teachers of Mazoon Al-Alam School, and the results of the study showed that the role of the Mozoon Al-Alam Award for Excellence and Educational Creativity in improving the educational (teaching) performance of female teachers in Mazoon Al-Alam School was with avery high degree. There are no statistically significant differences at the level of significance (0.05 ≥ α) between the averages of the study sample's responses to the questionnaire as a whole and to its domains due to the number of years of experience variable. In the light of the results of the study, the researcher recommended a number of recommendations, the most important of which were: Paying attention to preparing students who enjoy values and attitudes based on the faith of our nation through designing curricula and activities that enhance those values, and holding training courses that increase students' awareness of the mechanism of searching for information.